Sobre Sánchez, una biografía perezosa - Musitano, Julia (2018)
En este trabajo, me interesa resaltar la escritura biográfica de Osvaldo Baigorria (Sobre Sánchez) para pensar el vínculo entre biografía y literatura, por un lado, y la relación entre biógrafo y biografiado, por otro. La biografía de escritor (un escritor que escribe sobre otro escritor) puede definirse por la potencia imaginaria que une la obra y la vida del biografiado. Por eso, es importante observar allí el sentido de la aparición de lo autobiográfico: de la intromisión, a veces discreta a veces impune, del biógrafo en la vida del sujeto biografiado en proceso de construcción (el tercer capítulo de la biografía o "las notas al pie" constituyen la parte autorreferencial del texto), y simultáneamente la intrusión de la vida y la literatura del biografiado en los relatos del biógrafo (pienso en Con el sudor de tu frente y Anarquismo transhumante de Baigorria). Y, a partir de esto, específicamente, en Sobre Sánchez, quiero indagar en la elección de escribir sobre Néstor Sánchez y no sobre otro escritor y en la tensión entre el trabajo que conlleva la investigación de una vida y la pereza con la que construye Baigorria a su biografiado.
I am interested in outliningThis article outlines the biographical writing of Osvaldo Baigorria (Sobre Sánchez) in order to think aboutcontemplate the relationship connection between biography and literature, on the one sidehand, and between a biographer and its subjecta biographee, on the other. A writer´s biography (a writer who writes about another writer´s life) could define itself as the imaginary force that links the subject's life and work. That is the reason why it is important to observe there the meaning of the autobiographical emergencey of the autobiographical: the biographer's discreet or blatant intromission intrusion of the biographer into the life of itsthe subject's life in during the construction process (the third chapter of Sobre Sánchez or "las notas al pie" is the self-writing referential part of the text), and also the simultaneous intromission intrusion of the subject´s life and literature into the biographer'swriting of the writing biographer (I am thinking onfor instance, Con el sudor de tu frente and Anarquismo transhumante by Baigorria). I would like to inquire into Baigorria´s choice to write about Néstor Sánchez, and not aboutrather than someone elseany other writer, and into the tension between the work efforts involved in researching a life and the laziness with which Baigorria builds its his subject.
Keywords: Biografía; Osvaldo Baigorria; Néstor Sánchez; Pereza; Autofiguración; Biography; Osvaldo Baigorria; Néstor Sánchez; Laziness; Self-figuration